Comorbidities associated with Sjögren’s syndrome: Results from the Nationwide Inpatient Sample. - Koch, Terah; Al-Hashimi, Ibtisam; Koffman, Boyd M.; Deshpande, Abhishek; Khuder, Sadik A. (Translation: The University of Toledo Journal of Medical Sciences, 2014)
Although multiple comorbidities associated with Sjögren’s syndrome (SS) have been reported, reliable data regarding the prevalence of specific comorbidities among patients with SS remain sparse. In this study, we investigated the prevalence and risk for a broad spectrum of medical conditions among patients with SS in the United States. The Health Cost and Utilization Project (HCUP) Nationwide Inpatient Sample (NIS) data was utilized in order to investigate 29 different comorbidities among SS patients. Between the years 2007 to 2009 there were 19,127 admissions with SS listed as principal diagnosis (1.3%) and secondary diagnosis (98.7%). Compared with 57,381 controls, SS patients had significantly higher prevalence of lymphoma (OR 1.6), valvular disease (OR 1.42), congestive heart failure (OR 1.28), hypothyroidism (OR 1.24), paralysis (OR 1.24), deficiency anemia (OR 1.16), depression (OR 1.18), neurological disorders (OR 1.17), and chronic pulmonary disease (OR 1.07). SS is associated with substantial medical conditions that may impact morbidity and mortality as well as quality of life for individuals suffering from SS.